2019
DOI: 10.1111/jipb.12760
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT‐dependent vacuolar sorting and degradation of the auxin biosynthetic enzyme YUC1 flavin monooxygenase

Abstract: Summary YUC flavin monooxygenases catalyze the rate‐limiting step of auxin biosynthesis. Here we report the vacuolar targeting and degradation of GFP‐YUC1. GFP‐YUC1 fusion expressed in Arabidopsis protoplasts or transgenic plants was primarily localized in vacuoles. Surprisingly, we established that GFP‐YUC1, a soluble protein, was sorted to vacuoles through the ESCRT pathway, which has long been recognized for sorting and targeting integral membrane proteins. We further show that GFP‐YUC1 was ubiquitinated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The major and canonical function of ESCRT is to capture and sort ubiquitinated membrane proteins into the intraluminal vesicles (ILVs) within MVBs, which then fuse with the vacuole and release the ILV-containing membrane cargo into the vacuolar lumen for degradation (Spitzer et al 2009;Buono et al 2016;Gao et al 2017;Vietri et al 2019). The ESCRT machinery in plants regulates the sorting and vacuolar trafficking of some plant-specific soluble cargos, such as the abscisic acid (ABA) receptors PYR/PYL/RCAR and the auxin biosynthesis enzyme YUC1 flavin monooxygenase (Belda-Palazon et al 2016;Yu et al 2016;Yu and Xie 2017;Ge et al 2019;Chen et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The major and canonical function of ESCRT is to capture and sort ubiquitinated membrane proteins into the intraluminal vesicles (ILVs) within MVBs, which then fuse with the vacuole and release the ILV-containing membrane cargo into the vacuolar lumen for degradation (Spitzer et al 2009;Buono et al 2016;Gao et al 2017;Vietri et al 2019). The ESCRT machinery in plants regulates the sorting and vacuolar trafficking of some plant-specific soluble cargos, such as the abscisic acid (ABA) receptors PYR/PYL/RCAR and the auxin biosynthesis enzyme YUC1 flavin monooxygenase (Belda-Palazon et al 2016;Yu et al 2016;Yu and Xie 2017;Ge et al 2019;Chen et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The ESCRT machinery is required for sorting the ubiquitinated cargo proteins into invaginations of endosome membranes, and eventually degradation in the lysosome/vacuole (Raiborg and Stenmark, 2009; Otegui, 2018). It was also demonstrated that YUC1 was sorted to vacuoles for degradation through the ESCRT pathway (Ge et al ., 2018). In this study, we show that VPS28A and VPS28B play essential roles in endosomal trafficking of PINs.…”
Section: Discussionmentioning
confidence: 99%
“…AtBRO1 also interacts with the ESCRT‐III component SNF7, and recruits the DUb enzyme to late endosomes to remove ubiquitin from ubiquitinated cargoes before internalization of the cargoes into ILVs (Cardona‐Lopez et al ., 2015; Kalinowska et al ., 2015). It was shown that the auxin‐biosynthetic enzyme YUC1 flavin monooxygenase, a soluble protein, is sorted to vacuoles through the ESCRT pathway (Ge et al ., 2018). These studies indicated that ESCRT machinery plays important roles in plant growth and development (Gao et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides autophagy, the endosomal sorting complex required for transport (ESCRT) complex also regulates protein sorting to the vacuole, which is significant to multivesicular body (MVB) biogenesis and MVB-mediated vacuolar transport pathway [9,10]. Cell membrane proteins like the receptors and transporters are internalized into vesicles and delivered to the trans-Golgi network (TGN), which is defined as the early endosome in plants [11,12]. Depending on the demand, some TGN-localized proteins are recycled back to the cell membrane, while others are further transported to the late endosome, MVB, where those degraded membrane proteins are sorted to the intraluminal vesicles (ILVs) inside the MVB.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the demand, some TGN-localized proteins are recycled back to the cell membrane, while others are further transported to the late endosome, MVB, where those degraded membrane proteins are sorted to the intraluminal vesicles (ILVs) inside the MVB. Finally, the ILVs are released to the vacuolar lumen for degradation upon the fusion between the MVB and the vacuole [12,13]. During this process, the ESCRT complex plays essential roles in the sorting of ubiquitinated membrane proteins and the deformation of the MVB membrane to form ILVs [14,15].…”
Section: Introductionmentioning
confidence: 99%